Just Following Orders: A Meta-Analysis of the Correlates of American Police Officer Use of Force Decisions - Bolger, P. Colin (American journal of criminal justice, 2015)
A substantial amount of research has been conducted to identify the most influential predictors of police use of force decisions. Attempts to summarize this research, however, have so far been primarily limited to narrative literature reviews. While these works are important contributions, they are unable to ensure objectivity during their assessment of the status of the use of force empirical literature. This study improves upon prior research by using the meta-analytic method to identify the key correlates of police decisions to use force. This analysis identifies encounter characteristics as the category of variables that is most strongly correlated with use of force decisions, but also point to a strong localization effect. These findings therefore suggest that the primary focus for future theories of use of force decisions should be on what happens during the encounter, and adequate research syntheses will only be made possible when the number of datasets used to examine use of force decision-making is increased.